A high-resolution multiband survey of Westerlund 2 with the Hubble Space Telescope: II. Mass accretion in the pre-main-sequence population - Zeidler, Peter; Grebel, Eva K.; Pasquali, Anna (The astronomical journal, 2016)
We present a detailed analysis of the pre-main-sequence (PMS) population of the young star cluster Westerlund 2 (Wd2), the central ionizing cluster of the H ii region RCW 49, using data from a high-resolution multiband survey with the Hubble Space Telescope . The data were acquired with the Advanced Camera for Surveys in the F 555 W , F 814 W , and F 658 N filters and with the Wide Field Camera 3 in the F 125 W , F 160 W , and F 128 N filters. We find a mean age of the region of 1.04 ± 0.72 Myr. The combination of dereddened F 555 W and F 814 W photometry in combination with F 658 N photometry allows us to study and identify stars with H α excess emission. With a careful selection of 240 bona-fide PMS H α excess emitters we were able to determine their H α luminosity, which has a mean value ##IMG## [http://ej.iop.org/images/1538-3881/152/4/84/ajaa2fb7ieqn1.gif] $L(\rmHα )=1.67× 10^-31\,\rmerg\,\rms^-1$ . Using the PARSEC 1.2S isochrones to obtain the stellar parameters of the PMS stars, we determined a mean mass accretion rate ##IMG## [http://ej.iop.org/images/1538-3881/152/4/84/ajaa2fb7ieqn2.gif] $\dotM_\rmacc=4.43× 10^-8\,M_ødot \,\rmyr^-1$ per star. A careful analysis of the spatial dependence of the mass accretion rate suggests that this rate is ∼25% lower in the center of the two density peaks of Wd2 in close proximity to the luminous OB stars, compared to the Wd2 average. This rate is higher with increasing distance from the OB stars, indicating that the PMS accretion disks are being rapidly destroyed by the far-ultraviolet radiation emitted by the OB population.